Style, fashion, and local clothing brands amongst young Singaporean women - Tay, Xin Yi (Nanyang Technological University, 2023)
Style is an everchanging element of one’s self-concept and an integral part of women’s lives. Living in a digital age, social media becomes paramount in contributing to notions of style and fashion through targeted marketing and independent content creation. This study examines the popularity of local clothing brands within young Singaporean women and their ideas of style and fashion. Through qualitative in-depth interviews with 10 women aged 22 to 26 years old and thematic analysis of social media pages, findings reveal that while ideas of fashion is largely individualistic, it is heavily influenced by content sharing online. Furthermore, local blogshops have become increasingly adept in capturing the attention and interest of young Singaporean women. These findings amalgamate the wider existing literature on shopping, fashion, style, and the blogshop phenomenon in Singapore and the region.